Effects of Online and Offline Learning and Interest Learning on Learning Outcomes - Irawan Setiya Widodo; Atiqoh Atiqoh; Yoso Wiyarno (Journal on Education, 2023)
The purpose of this study was to find out the differences in (1) the results of online and offline learning in Class V students, (2) the learning outcomes of students with high and low interest in Class V students and, (3) the interaction between online and offline learning and learning interest on student learning outcomes. This study used an experiment where the research group was divided into two classes, namely online learning classes and offline learning combined with students who had high, medium and low interest. Data collection techniques through questionnaires and tests, where the population and sample used were fifth grade students of 66 students. This study used the 2-way Anova data analysis technique. Based on the calculation of the 2-way analysis obtained: (1) There is a significant difference between online learning and offline learning on student learning outcomes, (2) there is a significant difference in learning interest on student outcomes, and (3) There is a significant interaction between online learning and offline learning and interest in learning on student learning outcomes. Based on the results of this study, it was concluded that online learning and learning interest in student outcomes can improve student learning outcomes.